Analisis Service Quality Sistem Pelayanan Walk Thru Pada Kantor Bersama Samsat Kota Probolinggo - Mastina Maksin (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
In 2023, Indonesia will experience an increase in the number of motorbike transportation owners, this will have an impact on the process of paying motorbike tax. One of the things that happened in the city of Probolinggo was that there was a decrease in taxpayer awareness in paying vehicle tax, so the researcher had the aim of analyzing the Service Quality of the Walk Thru service system in the Probolinggo City Samsat joint office and identifying inhibiting factors for the Walk Thru service system in the Probolinggo City Samsat joint office. . The research method in this study uses a qualitative descriptive approach. There are findings in this research which researchers analyzed using five dimensions of Service Quality to measure its success, namely that there were poor findings in the assurance dimension which had an impact on service quality and for inhibiting factors, there was a lack of intensive socialization to the community so there needed to be improvements in that matter.